Globally asynchronous sulphur isotope signals require re-definition of the Great Oxidation Event - Pascal Philippot (Nature Portfolio, 2018)
The Great Oxidation Event (GOE) is considered to have occurred at 2.33–2.32 Ga based on the last occurrence of MIF-S in South Africa. Here, based on sulphur isotope analysis of samples from Western Australia, the authors show preservation of MIF-S beyond 2.31 Ga and call for a re-evaluation of GOE timing.